2003
DOI: 10.1021/ol035053a
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization and Reuse of Pd Complexes in Ionic Liquid:  Efficient Catalytic Asymmetric Fluorination and Michael Reactions with β-Ketoesters

Abstract: [reaction: see text] Palladium complexes (1 and 2) were immobilized in ionic liquids, and their applications to catalytic asymmetric fluorination and Michael reaction of beta-ketoesters were successfully demonstrated. This immobilization enabled the reuse of the catalysts no less than 10 times in fluorination and 5 times in Michael reaction with levels of efficiency comparable to those obtained in usual organic solvents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 149 publications
(51 citation statements)
references
References 12 publications
0
48
0
3
Order By: Relevance
“…[27] Previously, Sodeoka and co-workers showed that ionic liquids could be efficient media for the palladium-catalyzed fluorination reaction of b-keto esters. [28] The reaction was found to be as efficient as in ethanol, although longer reaction times were required. Moreover, the catalyst was found to be recyclable up to ten times without affecting the yield or the enantioselectivity.…”
Section: Fluorination Of B-ketophosphonatesmentioning
confidence: 94%
“…[27] Previously, Sodeoka and co-workers showed that ionic liquids could be efficient media for the palladium-catalyzed fluorination reaction of b-keto esters. [28] The reaction was found to be as efficient as in ethanol, although longer reaction times were required. Moreover, the catalyst was found to be recyclable up to ten times without affecting the yield or the enantioselectivity.…”
Section: Fluorination Of B-ketophosphonatesmentioning
confidence: 94%
“…[61][62][63][64] However, continuing exploitation of novel catalysts, including metal complexes and organic catalysts, is necessary to meet the need for various chiral fluorinated compounds, many of which are expected to find applications in the fields of medicinal chemistry, chemical biology, and material sciences. 65) While we could use environmentally friendly solvents, such as EtOH and water, recovery of the Pd complexes from the reaction mixtures was not easy. Therefore we decided to examine immobilization and reuse of the Pd complexes.…”
Section: Catalytic Enantioselective Fluorination Of Oxindole Derivativesmentioning
confidence: 99%
“…[14] The catalysts are water-tolerant and have been shown to catalyze the reaction with equal facility in ionic liquids. [15] The authors have also demonstrated the utility of their method by reduction of the product ketones to α-fluoro-β-hydroxy esters, then subsequent conversion to α-fluoro-β-amino esters. (3) As a complement to Sodeoka's findings, Cahard evaluated chiral bis(oxazoline)copper complexes as catalysts for the formation of α-fluoro-β-keto esters [Equation (4)].…”
Section: Microreviewmentioning
confidence: 99%